Power dynamics in transaction platforms: Adaptive strategies of platform-dependent entrepreneurs - Futonge Nzembayie, Kisito; Evers, Natasha (My University, 2024)
This study investigates the adaptive strategies of platform-dependent entrepreneurs (PDEs) to mitigate venture survival risks associated with power asymmetries on transaction platforms. Using an embedded single case study design, we explore the decade-long survival of a PDE's firm in EdTech, focusing on its relationship with two dominant platforms, Google Search and AdSense. Our findings culminate in a robust framework that elucidates the strategic responses of PDEs to the challenges of power imbalance and its exercise through platform governance. Critically, the study reveals that PDEs assert their self-determination in a two-step process that is best observed over time. Strategic subjectification, followed by multihoming and diversification, can be observed over a long temporal duration, emerging as crucial mechanisms for managing dependency risks. This study contributes to the platform strategy literature by shifting the focus from owners to participants, simultaneously illuminating entrepreneurial resilience amid power-related uncertainties.
PUBLISHED
Keywords: platforms; power asymmetries; governance; entrepreneurship; transaction platforms; Digital Engagement; Digital Humanities; Digital Platform; Entrepreneurship; Innovation